Optimized Effects of Fisetin and Hydroxychloroquine on ER Stress and Autophagy in Nonalcoholic Fatty Pancreas Disease in Mice - Mahboobe Sattari; Amin Karimpour; Maryam Akhavan Taheri; Bagher Larijani; Reza Meshkani; Ozra Tabatabaei-Malazy; Ghodratollah Panahi (Journal of Diabetes Research)
Conclusion: Our study reveals that FSN and HCQ effectively combat HFD-induced NAFPD, improving insulin sensitivity and addressing pancreatic fat deposition linked to metabolic syndrome. While HCQ may cause endoplasmic reticulum stress, FSN offers protective effects, supporting their combined use for better treatment outcomes.